Public perceptions of demand side management and a smarter energy future - Spence, Alexa; Demski, Christina; Butler, Catherine; Parkhill, Karen; Pidgeon, Nick (Nature Publishing Group, 2015)
Demand side management (DSM) is a key aspect of many future energy system scenarios1,2. DSM refers to a range of technologies and interventions designed to create greater efficiency and flexibility on the demand side of the energy system3. Examples include the provision of more information to users to support efficient behaviour and new ‘smart’ technologies that can be automatically controlled. Key stated outcomes of implementing DSM are benefits for consumers, such as cost savings3, 4 and greater control over energy use. Here, we use results from an online survey to examine public perceptions and acceptability of a range of current DSM possibilities in a representative sample of the British population (N = 2441). We show that, whilst cost is likely to be a significant reason for many people to uptake DSM measures, those concerned about energy costs are actually less likely to accept DSM. Notably, individuals concerned about climate change are more likely to be accepting. A significant proportion of people, particularly those concerned about affordability, indicated unwillingness or concerns about sharing energy data, a necessity for many forms of DSM. We conclude substantial public engagement and further policy development is required for widespread DSM implementation.